2015
DOI: 10.3823/1768
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Association between Polymorphisms in Osteoprotegerin Gene and Risk of Low Bone Mineral Density

Abstract: Background: Low bone mineral density (BMD) predisposes to os-teoporosis and elevated risk of fractures. Osteoprotegerin is a soluble molecule associated to metabolism of bone tissue with inhibition of osteoclast-differentiation. Several studies determined the relation among polymorphisms in osteoprotegerin gene and low BMD, but the results are contradictory, so an evaluation about these polymorphisms is necessary. This study carried out a meta-analysis to four polymor-phisms in osteoprotegerin gene (A163G, G11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…T245G (rs3134069). This SNP is present in the promoter region (5 0 UTR) of the TNFRSF11B (OPG) gene for analysis; such polymorphism is associated with osteoporosis and other bone-related conditions [9,17].…”
Section: A163g (Rs3102735)mentioning
confidence: 99%
See 2 more Smart Citations
“…T245G (rs3134069). This SNP is present in the promoter region (5 0 UTR) of the TNFRSF11B (OPG) gene for analysis; such polymorphism is associated with osteoporosis and other bone-related conditions [9,17].…”
Section: A163g (Rs3102735)mentioning
confidence: 99%
“…Another study suggested that the OPG/A163G polymorphism participates in the genetic control of bone homeostasis among the Slovak population and can raise or lower the risk of osteoporosis in such individuals [ 7 ]. Different meta-analyses (MA) have shown that the G allele of the OPG A163G and T245G polymorphisms might increase osteoporosis risk [ 8 , 9 ]. One interesting study displayed that A163G and T245G were linked to augmented fracture risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation